Towards Legal Literacy for HR Professionals in Building Law-Aware Organizational Management Systems - Uzma Abbas (Journal of Advanced Research in HR and Organizational Management, 2025)
Legal literacy has emerged as a critical competency for human resource professionals in contemporary organisational environments characterised by complex regulatory frameworks and heightened compliance requirements. This review examines the intersection of legal knowledge, HR practice, and organisational management systems, synthesising research on how legal literacy influences HR decision-making, risk management, and strategic organisational outcomes. The paper explores the conceptual foundations of legal literacy in HR contexts, examines empirical evidence on its impact on organisational performance, and identifies key dimensions of law-aware management systems. Findings suggest that HR professionals with enhanced legal literacy contribute significantly to organisational compliance, employee relations, and strategic value creation, though significant gaps remain in training and development approaches.